2002
DOI: 10.1103/physrevlett.88.246101
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Forces in Branched Molecular Liquids

Abstract: The solvation force of squalane confined between a silicon tip and a graphite surface has been measured by atomic force microscopy. This highly branched molecule shows oscillatory force profiles similar to those of spherical and linear chain molecules. Squalane molecules closest to the substrate are tightly bound and finer details imply that interdigitation occurs. This agrees with computer simulations for branched molecules but differs qualitatively from force balance experiments. These differences arise from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 24 publications
5
43
0
Order By: Relevance
“…The same appears to be true for squalane as shown in figure 7(c). This observation further validates the measurements of Granick et al [33] (using SFA) and lately by Lim and O'Shea [34] (using AFM), showing oscillatory forces exist for branched molecules such as squalane and 3-methylundecane (C12H26).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The same appears to be true for squalane as shown in figure 7(c). This observation further validates the measurements of Granick et al [33] (using SFA) and lately by Lim and O'Shea [34] (using AFM), showing oscillatory forces exist for branched molecules such as squalane and 3-methylundecane (C12H26).…”
Section: Resultssupporting
confidence: 77%
“…This effect depends on the packing density of the molecules within the conjunction, which is a complex function of the sliding velocity, and seems to be only effective over a range of speeds (molecular layers), before a bulk lubricant film of hydrodynamic characteristics is formed. This finding is in line with the experimental works in [7,8,9,34] and complex numerical analysis, such as that for a progressively diminishing gap by Teodorescu et al [35]. The main contribution of this paper is in demonstrating that such characteristics can be predicted using a relatively simple analytical approach, based on the assumption of a Langmuir-Blodgett layer subjected to Eyring thermal activation energies.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…During recent years solvation forces in different liquids were studied with the AFM [741][742][743][744][745][746]. Examples are OMCTS (octamethyl-cyclo-tetra-siloxane) [747,748], 1,3,5-trimethylbenzene ((CH 3 ) 3 C 6 H 3 ) [747], and n-alcohols [749][750][751].…”
Section: Solvation Forcesmentioning
confidence: 99%
“…Studies on branched alkanes remain controversial. Early research suggested there was no solvation layering for branched molecules [6,7], but more recent simulations [4,[8][9][10][11][12][13][14] and experimental studies [15][16][17][18][19] show that this is not necessarily the case. However, if such solvation layers do occur, the confined molecules tend to be more ''liquid-like'' in comparison to corresponding linear alkanes due to poorer inplane ordering [4,[9][10][11]13,14].…”
mentioning
confidence: 99%